Make or buy to innovate in the software sector - Morero, Hernán Alejandro; Ortiz, Pablo Arnaldo; Wyss, Federico (2022)
Fil: Morero, Hernán Alejandro. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.